2017
DOI: 10.1007/s00787-017-0985-z
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the determinants of perceived quality in outpatient child and adolescent mental health services from the perspectives of parents and patients

Abstract: This cross-sectional survey adopting a multiple-informant perspective explores the factors that influence perceived quality (i.e., therapeutic alliance and satisfaction) in an outpatient setting within child and adolescent mental health services (CAMHS). A total of 1433 participants (parents, n = 770, and patients, n = 663) attending or having attended (drop-out) outpatient units participated in the study. The outcome measures were satisfaction (Client Satisfaction Questionnaire) and the therapeutic alliance (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
2
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(54 citation statements)
references
References 45 publications
2
41
2
9
Order By: Relevance
“…Polite and sympathetic provider behaviour makes the patient feel comfortable [4, 7]. Other studies conducted among OPD patients in Iran and Europe have found that a feeling of reassurance is related to a positive perception of care quality by both patients and parents [9] and patient satisfaction increases with perceived provider empathy and explanations [2, 8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polite and sympathetic provider behaviour makes the patient feel comfortable [4, 7]. Other studies conducted among OPD patients in Iran and Europe have found that a feeling of reassurance is related to a positive perception of care quality by both patients and parents [9] and patient satisfaction increases with perceived provider empathy and explanations [2, 8].…”
Section: Discussionmentioning
confidence: 99%
“…Future utilization of psychiatric services depends on how satisfied patients are with the services received [4]. So, by understanding the patients’ perspective, a better quality, patient-centred health care can be delivered and premature termination of therapy can be avoided [9].…”
Section: Introductionmentioning
confidence: 99%
“…There has been an ongoing shift in the direction of shared decision-making and person-centered treatment in adolescent mental healthcare (10,15,16). Shared decision-making is associated with patient engagement and perceived quality and satisfaction with the healthcare services (8,17,18). However, most research on shared decision-making have focused on implementation and experiences with decision aids, while little is known about mental health outcomes (18).…”
Section: Introductionmentioning
confidence: 99%
“…There is also a dearth of research in adolescent mental healthcare and adolescents' perspectives (19,20). Previous qualitative research with adolescents highlights the importance of providing mental health services that incorporate individual expectations, needs, and goals (8,21,22). Research should also explore how and if person-centered care contributes to recovery and a reduction in the use of restraints (23).…”
Section: Introductionmentioning
confidence: 99%
“…There are not many studies conducted to parents' single visit experiences in child psychiatric clinic, as earlier studies focused mostly on the predictors of satisfaction, stages or results of care. Satisfaction can be predicted strongest from encountering parents' met expectations and strain, other notable predictors are parents' optimism and improvement with their child's condition (10)(11)(12)(13). Based on healthcare districts own reports and previous studies in Finland, the psychiatric services for children have been satisfied for both, parents 0 and children (14,15).…”
Section: Introductionmentioning
confidence: 99%